Preserving professional identity: teachers’ voices and internal struggle on the discourse of the kurikulum merdeka - Amaliyah Ulfah; M.Tolkhah Adityas (Universitas Ahmad Dahlan, 2023)
This qualitative study explores the experiences and perspectives of teachers in implementing the Kurikulum Merdeka, an independent curriculum movement in Indonesia. The study aims to understand how teachers navigate the challenges associated with the implementation process while preserving their professional identity. This research will employ a hermeneutic phenomenological approach which involves transcription, thematic analysis, and interpretation and meaning-making. The approach will provide a robust framework for exploring teachers’ lived experiences in relation to the implementation of the curriculum. The methodology involved in-depth interviews with the teachers who have been actively involved in the implementation of the Kurikulum Merdeka in their schools. The findings show the dynamic and dialogic responses of teachers to educational reforms like Kurikulum Merdeka. It applies Bakhtin's theory of dialogism to uncover themes and sub-themes in teachers' narratives. These themes include the adaptation of teaching roles and conflicts stemming from traditional training versus new approaches. Social interactions and support from colleagues, as well as changes in the student-teacher dynamic, are vital aspects. Challenges like letting go of control and finding a balance in guiding students are discussed, along with strategies for navigating these challenges. The discussion emphasizes the evolution of professional identity as a result of ongoing dialogues in response to educational changes.